-77=7(y-6)

Simple and best practice solution for -77=7(y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -77=7(y-6) equation:



-77=7(y-6)
We move all terms to the left:
-77-(7(y-6))=0
We calculate terms in parentheses: -(7(y-6)), so:
7(y-6)
We multiply parentheses
7y-42
Back to the equation:
-(7y-42)
We get rid of parentheses
-7y+42-77=0
We add all the numbers together, and all the variables
-7y-35=0
We move all terms containing y to the left, all other terms to the right
-7y=35
y=35/-7
y=-5

See similar equations:

| 6x^2-73=0 | | 4x+17=2x−5 | | `3x-7=3x+1` | | 2.1+0.7*x=9.8 | | 2(3x+12)=16 | | 2y-8=3y-16 | | 4b+3=6b | | 3x-12=3;x=5 | | 5x+21=173 | | p+18=37 | | 17=a/8 | | X2+3y2=43 | | w+56=81 | | n=16+19 | | `-2m+8+m+1=0` | | 15m=-90 | | 4=3+x/5 | | c-28=-6 | | 1.3/6.5=60/x | | P=1.20x-361+3.30x | | 1.4=g+4.1÷-2 | | 2x2+1=-163 | | 13x/2+50=180 | | 3+10d=7+9d | | -8-4h=10-6h | | x2+2x–8=0 | | 4/5a-8=a+2 | | 9x–6+x2=2 | | 9x–6+x/2=2 | | T=18x+2B | | 29=1/2(11x+2)+23 | | -10-7u=-10u+5 |

Equations solver categories